Keharmonisan Keluarga Petani dan Pedagang Ditinjau Dari Faktor Ekonomi - Putri Anugrah; H. Ahmad Tadjudin; Sofia Gussevi (Yayasan Cendekia Gagayunan Indonesia, 2024)
Marriage is a forum for forming a sakinah, mawaddah and warrahmah family in which there needs to be a sense of trust and responsibility in carrying out their respective roles in relation to the rights and obligations of both husband and wife to achieve happiness in this world and the hereafter. Having a harmonious family is every family's dream. However, achieving a harmonious family is influenced by several factors. Economic factors play a role in meeting family needs and many cases of divorce occur in society due to poor economic conditions. Based on this, researchers conducted research on Farmers and Traders in Lebak Anyar Village whose families are harmonious and have survived for a long time to this day despite unstable economic conditions. The aim of this research is to determine and describe the factors and efforts of farmers and traders in forming a harmonious family, even though the economic situation is unstable and income uncertainty, this is not the reason for forming a harmonious family.